(untitled) (Comprehensive Journal of Science, 2025)
We extracted in this research the extent to which we benefited from the photovoltaic energy in cooling according to the climatic in easterly Libya, considering the east a desert region,as is known agricultural and industrial drying in libya relies heavily on open sun drying or on fossil fuels which causes quality and quantity losses and increases the consumption of non renewable energies libya has significant solar potential that makes renewable energy based solutions especially solar systems highly viable the design of the photovoltaic system and the calculation of solar radiation over a whole year, and from the economic feasibility to show us that the use of photovoltaic energy In cooling, it is of good quality and high efficiency in southern Libya, but it is relatively expensive compared to the price of electrical energy in the public network, given that Libya is a country rich in oil resources, and also provides full independence.